Racialized Burdens: Applying Racialized Organization Theory to the Administrative State. (29th January 2022) - Ray, Victor; Herd, Pamela; Moynihan, Donald
Abstract: This article develops the concept of racialized burdens as a means of examining the role of race in administrative practice. Racialized burdens are the experience of learning, compliance and psychological costs that serve as inequality reproducing mechanisms. To develop this concept, we examine administrative burdens in the US state from the theoretical perspective of racialized organizations. Using examples from attempts to access citizenship rights—via immigration, voting and the social safety net—we illustrate some key points. First, racialized burdens combine control of access to resources and ideas about racial groups in ways that typically disadvantage racially marginalized groups. Second, while still promising fair and equal treatment, racially disproportionate burdens can be laundered through facially neutral rules and via claims that burdens are necessary for unrelated reasons. Third, racialized burdens emerge when more explicit forms of racial bias in policies or administrative practices become illegal, politically untenable or culturally unacceptable. Racialized burdens neatly carry out the "how" in the production of racial inequality while concealing, or providing an alibi for, the "why."